Nation as a Neo-Idol: Muslim Political Theology and the Critique of Secular Nationalism in Modern South Asia - Rehman, Mohammad Adnan (Religions, 2018)
Modern perspectives on nationalism tend to privilege structuralist readings which approach nationalism as entailing economic and political restructuring, thereby overlooking the necessary role of human factors in the functioning of nationalism. Religious opposition to secular nationalism is then condemned as backward, reactionary, fundamentalist, or ideological. However, a different understanding of nationalism is uncovered when the role of human factors in nationalism are scrutinized. Toward discerning the role of human factors in nationalism and its relation to religion in general, I turn to Liah Greenfeld's analysis of social psychology of nationalism as a secular ideology. In exploring the effects of nationalist ideology on religion, I return to the earliest Muslim debates on nationalism in South Asia between two critics of nationalism, Muhammad Iqbal and Abu'l A'laa Mawdudi, and their opponents, Abul Kalam Azad and Husayn Ahmad Madani.